Ergonomic analysis for a regional aircraft interior design. - Flavia Renata Dantas Alves Silva (2007)
The purpose of this work is to develop a preliminary interior design of a regional aircraft considering ergonomic and cost aspects. The use of virtual humans provides a better interpretation of the aircraft interior environment, making possible to simulate movements and passenger comfort aspects. The importance of this study becomes evident through the necessity of the aircraft manufacturer of predicting human behavior during all the flight phases. This text also aims to present the difficulty to accomplish the design requirements and at same time meet the market expectations without oversizing the aircraft. The dissertation is applied to an aircraft (called "Unique") developed in the context of the EMBRAER Engineering Specialization Program (PEE) and includes different features of the aircraft interior environment as: cross section definition, seat configuration and passenger cabin layout. The ergonomics analysis comprises the living space (distance between seats) and oxygen mask accessibility. The used method was RULA tool (available in the Catia V5 package) that evaluate individuals' exposures to limb disorders like postures, forces and muscle activities that have been shown to contribute to Repetitive Strain Injuries (RSIs). A preliminary cost analysis is also presented by comparing a standard (30 pax at 32" seat pitch) and an advanced (28 pax at 30"/36" seat pitch) aircraft interior configuration.